Posting Traditional Ecological Knowledge on Open Access Biodiversity Platforms: Implications for Learning Design - Funk, Johanna; Guthadjaka, Kathy; Kong, Gary (The Australian Journal of Indigenous Education, 2015)
BowerBird is an open platform biodiversity website (http://www.BowerBird.org.au) and a nationally funded project under management of the Atlas of Living Australia (ALA) and Museum Victoria. Members post sightings and information about local species of plants and animals, and record other features of ecosystems. Charles Darwin University's Northern Institute Elder on Country researcher, Kathy Guthadjaka, has shared pictures and information about the biodiversity of her homelands in the Yolŋu community of Gäwa, on Elcho Island in north east Arnhem Land, Northern Territory. The extent to which this knowledge can be exposed in the same way as other open resources, can pose dilemmas about the level of ‘openness’ that is appropriate. Open sharing of educational materials can be promoted as a basic human right. This paper will explore the extent to which traditional knowledge can be made openly available. What are the implications for sharing this knowledge in a westernised context that compartmentalises it, and how can a western academic perspective learn from this knowledge and engage functionally with it for the purposes of learning? The existence of this project on the interface between traditional knowledge and western technocratic information management also has implications for how information is presented and valued.